Hadis-Hadis Tentang ‘Ain : Penyakit ‘Ain Perspektif Ibnu Qayyim Al-Jauziyyah dan Relevansinya Terhadap Media Sosial - Mufida, Ayunda Cahya; Mahar, Muhammad Hasnan (STAI Darul Kamal NW Kembang Kerang, 2023)
This research is motivated by the advances in technology and information enabling easier communication through messages, photos, videos, and others. However, this phenomenon causes negative impacts to arise such as the emergence of jealousy and amazement feeling that is not based on the greatness of Allah which is known as ‘Ain illness. ‘Ain illness is not widely known by people in general, but it can be studied in hadiths by referring to the hadiths of scholars, such as Imam Ibn Qayyim -rahimahullah in his various books, one of which is the Book of Zād Al-Ma'ad. This study aims to find out Ibn Qayyim's perspective on ‘Ain, how to prevent and treat it, as well as the impact of ‘Ain on something that is not seen directly.